The healthcare operators’ experience with aggressive patients and their visitors: a cross-sectional study in four clinical departments - Guglielmetti, Chiara; Gilardi, Silvia; Licata, Mario; De Luca, Giuseppe (La Medicina del Lavoro, 2016)
Background: Aggressive behaviour of patients and their relatives represent a risk factor for healthcare professionals. Objectives: The study aimed to explore the context of high risk departments (emergency department, psychiatric department) and of low risk departments (midwifery/paediatrics and outpatients clinic): a) the risk of exposure to various forms of aggression (physical, verbal, threats) by patients and their visitors towards healthcare professionals; b) how the healthcare professionals react to such aggressive events; c) the relationship between verbal aggression and healthcare professional burnout, compared to other work-related stressors. Methods: The cross-sectional study involved 620 healthcare workers in a hospital in northern Italy (47.7% redemption rate, equivalent to 296 subjects). The data were gathered through a self-report on-line questionnaire. Results: The risk of aggression, regardless of its form, was not dependent on the role of the healthcare professional, while risk  was lower for older professionals and for women. The risk index for emergency department health professionals was higher than the index for professionals in the other three areas. Perceived levels of verbal aggression in the midwifery/paediatrics department were similar to those in the psychiatric department. Verbal aggression was found to be linked to the three dimensions of burnout and to a higher contribution to depersonalisation. Conclusions: the study showed that specific prevention initiatives and health profession support are also needed in clinical departments traditionally considered at low risk.